2018
DOI: 10.1038/s41467-018-06796-9
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA-seq reveals profound transcriptional similarity between Barrett’s oesophagus and oesophageal submucosal glands

Abstract: Barrett’s oesophagus is a precursor of oesophageal adenocarcinoma. In this common condition, squamous epithelium in the oesophagus is replaced by columnar epithelium in response to acid reflux. Barrett’s oesophagus is highly heterogeneous and its relationships to normal tissues are unclear. Here we investigate the cellular complexity of Barrett’s oesophagus and the upper gastrointestinal tract using RNA-sequencing of single cells from multiple biopsies from six patients with Barrett’s oesophagus and two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 63 publications
5
74
3
Order By: Relevance
“…Furthermore, a recent study that investigated Barrett esophagus cellular complexity found a cell population that was enriched in LEFTY1 and expressed the intestinal stem cell marker OLFM4 [42]. Consistent with our results, these authors observed two patterns of LEFTY1 staining, (1) a strong and localized staining and (2) a moderate and diffuse staining [42]. Combined with our data, these different patterns of LEFTY1 staining could suggest that LEFTY1 has different roles in adult tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a recent study that investigated Barrett esophagus cellular complexity found a cell population that was enriched in LEFTY1 and expressed the intestinal stem cell marker OLFM4 [42]. Consistent with our results, these authors observed two patterns of LEFTY1 staining, (1) a strong and localized staining and (2) a moderate and diffuse staining [42]. Combined with our data, these different patterns of LEFTY1 staining could suggest that LEFTY1 has different roles in adult tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Advances in single cell technologies have recently provided new insights into the cellular and molecular diversity and pathological mechanisms underlying many diseases, including cancers, premalignant and non-malignant conditions (Baslan and Hicks, 2017;Owen et al, 2018;Parikh et al, 2019). Parallel interrogation of mutation status and transcriptome at a single-cell level provide unprecedented opportunity to identify cancer cell-specific targets (Giustacchini et al, 2017;Rodriguez-Meira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, the normal esophagus consists of a stratified squamous epithelium, but Barrett's differs significantly from this and instead resembles a columnar epithelium, typically found in the more distal gastrointestinal tract (for review, see Spechler and Souza 2014). Several models have been proposed for how this metaplastic transition occurs including transdifferentiation from normal esophageal epithelial cells (Stairs et al 2008;Vega et al 2014), colonization by migrating cells of gastric origin (Quante et al 2012), changes to cells from the gastroesophageal junction (GOJ) (Jiang et al 2017), or more recently, from cellular subpopulations within normal esophageal epithelia (Owen et al 2018).…”
mentioning
confidence: 99%